GWAS analysis to elucidate genetic composition underlying a photoperiod-insensitive rice population, North Korea - Jadamba, Chuluuntsetseg; Vea, Richie L.; Ryu, Jung-Hoon; Paek, Nam-Chon; Jang, Su; Chin, Joong Hyoun; Yoo, Soo-Cheul (Frontiers in Genetics, 2022)
Heading date (Hd) is one of the main factors determining rice production and regional adaptation. To identify the genetic factors involved in the wide regional adaptability of rice, we conducted a genome-wide association study (GWAS) with 190 North Korean rice accessions selected for non-precocious flowering in the Philippines, a low-latitude region. Using both linear mixed models (LMM) and fixed and random model circulating probability unification (FarmCPU), we identified five significant loci for Hd in trials in 2018 and 2019. Among the five lead single nucleotide polymorphisms (SNPs), three were located adjacent to the known Hd genes, Heading date 3a (Hd3a), Heading date 5 (Hd5), and GF14-c. In contrast, three SNPs were located in novel loci with minor effects on heading. Further GWAS analysis for photoperiod insensitivity (PS) revealed no significant genes associated with PS, supporting that this North Korean (NK) population is largely photoperiod-insensitive. Haplotyping analysis showed that more than 80% of the NK varieties harbored nonfunctional alleles of major Hd genes investigated, of which a nonfunctional allele of Heading date 1 (Hd1) was observed in 66% of the varieties. Geographical distribution analysis of Hd allele combination types showed that nonfunctional alleles of floral repressor Hd genes enabled rice cultivation in high-latitude regions. In contrast, Hd1 alleles largely contributed to the wide regional adaptation of rice varieties. In conclusion, an allelic combination of Hd genes is critical for rice cultivation across wide areas.